COVID-19, Stay-At-Home Orders and Employment: Evidence from CPS Data - Louis-Philippe Béland; Abel Brodeur; Taylor Wright (Institute of Labor Economics (IZA), 2020)
In this paper, we examine the short-term consequences of COVID-19 and evaluate the impacts of stay-at-home orders on employment and wages in the United States. Guided by a pre-analysis plan, we document that COVID-19 increased the unemployment rate, decreased hours of work and labor force participation, especially for younger workers, non-white, not married and less-educated workers. We built four indexes (exposure to disease, proximity to coworkers, work remotely and critical workers) to study the impact of COVID-19. We find that workers that can work remotely are significantly less likely to have their labor market outcomes affected, while workers working in proximity to coworkers are more affected. The unemployment effects are significantly larger for states that implemented stay-at-home orders. Our estimates suggest that, as of early May, these policies increased unemployment by nearly 4 percentage points, but reduced COVID-19 cases by 186,600– 311,000, and deaths by 17,851–23,325. We apply our estimates to compute lost income (18.6–21.4 billion), reduced government income tax revenues (3.4–5.5 billion), increased unemployment insurance benefit payments (5–5.8 billion) and reduced hospital costs (0.7–1.2 billion). Despite the jobs lost, age adjusted value of statistical life suggests that stay-at-home orders are cost effective.
Keywords: I15; I18; J21; 330; COVID-19; unemployment; wages; remote work; exposure to disease; essential workers; stay-at-home orders; lockdown